2011
DOI: 10.1590/s1806-66902011000300023
|View full text |Cite
|
Sign up to set email alerts
|

Manejo do solo e adubação nitrogenada na supressão de plantas daninhas na cultura do feijão de inverno e irrigado

Abstract: Resumo -Objetivou-se avaliar diferentes plantas de coberturas do solo e a adubação nitrogenada na supressão de plantas daninhas na cultura do feijão de inverno e irrigado. O delineamento experimental utilizado foi o de blocos casualizados em esquema de parcelas subdivididas, constituído por quatro blocos e quatro repetições. Nas parcelas foram utilizados manejos de cobertura de solo (milheto, crotalaria juncea, sem cobertura e vegetação espontânea). Nas subparcelas utilizou-se a presença e ausência de nitrogên… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
4
0
4
Order By: Relevance
“…Our results are in accordance with those observed by Albuquerque et al (2013), who identified that the straw of some crops reduced WDM when compared to a bare soil. Vincensi et al (2011) also obtained similar results.…”
Section: Resultssupporting
confidence: 63%
“…Our results are in accordance with those observed by Albuquerque et al (2013), who identified that the straw of some crops reduced WDM when compared to a bare soil. Vincensi et al (2011) also obtained similar results.…”
Section: Resultssupporting
confidence: 63%
“…No Brasil, a sua produtividade média sempre esteve abaixo de 1.000 kg ha -1 , embora nas lavouras tecnificadas sejam obtidos valores até três vezes superiores (IBGE, 2012). Muitos fatores têm sido aventados para a ocorrência dessa situação, entre os quais destaca-se a interferência negativa imposta por plantas daninhas à cultura (Vincensi et al, 2011). O feijão-comum é muito cultivado em pequenas e médias propriedades no País, onde o manejo dessas espécies nem sempre ocorre na intensidade correta ou no momento mais adequado.…”
Section: Introductionunclassified
“…They stimulated seed germination and emergence, which can be controlled; thus, the seedbank may be reduced in the soil (SOSBAI, 2016). Besides, soils without plant cover usually have higher temperature amplitude than soils protected by plant residues, thus, stimulating the germination process (VINCENSI et al, 2011), predation, deterioration and transport by several agents, which also contributes to reduce the seedbank. However, the conventional system made Oryza sativa have the highest values of importance value index, relative density and relative frequency.…”
Section: Resultsmentioning
confidence: 99%